2023
DOI: 10.3390/v15040900
|View full text |Cite
|
Sign up to set email alerts
|

The Modulation of Immune Responses in Tilapinevirus tilapiae-Infected Fish Cells through MAPK/ERK Signalling

Abstract: Tilapia lake virus (TiLV) is a novel RNA virus that has been causing substantial economic losses across the global tilapia industry. Despite extensive research on potential vaccines and disease control methods, the understanding of this viral infection and the associated host cell responses remains incomplete. In this study, the involvement of the mitogen-activated protein kinase/extracellular signal-regulated kinase (MAPK/ERK) pathway in the early stages of TiLV infection was investigated. The results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…Interestingly, in addition to the observed cellular damage, our findings revealed variations in the infection dynamics and TiLV replication across different fish cells. Notably, the TiLV load in the E-11 cells was higher than that in the RHTiB cells at 24 hpi, which is consistent with the results of a previous study 14 . We propose that while TiLV is capable of propagating in recently established RHTiB cells, these cells are less susceptible to TiLV compared to well-established E-11 cells.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Interestingly, in addition to the observed cellular damage, our findings revealed variations in the infection dynamics and TiLV replication across different fish cells. Notably, the TiLV load in the E-11 cells was higher than that in the RHTiB cells at 24 hpi, which is consistent with the results of a previous study 14 . We propose that while TiLV is capable of propagating in recently established RHTiB cells, these cells are less susceptible to TiLV compared to well-established E-11 cells.…”
Section: Discussionsupporting
confidence: 92%
“…The E-11 and RHTiB cells were assessed for TiLV at 10 min post-infection (mpi), 30 mpi, 1 h postinfection (hpi), 3 hpi, 6 hpi, and 24 hpi using a quantitative reverse transcription polymerase chain reaction (RT-qPCR). Initially, total RNA extraction from the collected cell lysates was conducted as described by Lertwanakarn et al 14 Briefly, the cell lysates were mixed with GENEzol® reagent (Geneaid Biotech, Taipei, Taiwan) and chloroform (Sigma-Aldrich, Saint-Louis, USA) and centrifuged at 15,000 × g at 4 °C. The supernatant was collected and treated with DNase I (Thermo Fisher Scientific, Carlsbad, USA), followed by 2-propanol (Merck, Darmstadt, Germany), and stored at −20 °C for 2 h. After thawing and centrifugation, the pellets were washed with ethanol and air-dried.…”
Section: Tilv Rna Quantification In Cells and Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, TEM studies revealed the presence of TiLV particles in the liver of infected fish, in both laboratory and natural settings, although the specific mechanism of cell entry remains undetermined ( Del-Pozo et al, 2017 ; Tattiyapong, Dachavichitlead & Surachetpong, 2017 ). Recent reports demonstrated that TiLV enters tilapia cells via a cholesterol-dependent, dynamin-mediated endocytosis mechanism ( Abu Rass et al, 2022 ) and MAPK-dependent signaling pathway ( Lertwanakarn et al, 2023 ). In our study, we observed notable changes in the intracellular structure and organelles of infected E-11 cells within 1 dpi.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that TiLV might cross the BBB in a process dependent on actin and microtubule polymerization, both known to be involved in the formation of macropinosome ruffles. Moreover, similar to HIV-1, ERK/MAPK signalling participates in TiLV propagation [ 93 ].…”
Section: Tilv Transmission and Cns-invasionmentioning
confidence: 99%